Socio-digital participation, friendship and academic support among sixth to ninth graders in Finland - Li, Shupin (fi=Turun yliopisto|en=University of Turku|, 2019)
This dissertation examined how Finnish students’ socio-digital participation (i.e.engagement and practices with social media and the Internet on mobile devices and computers) is related to their friendships and academic support among peers. In particular, the purposes were to study the similarity effects between gender and across cultural backgrounds in face-to-face, Facebook contact and peer academic support networks; to uncover the effects of peer selection and influence in the development of students’ peer friendship networks and their socio-digital participation; and to explore the different profiles of socio-digital practices related to social networks. Participants were students from grades six to nine in southern Finland. The data were collected using a social networking questionnaire, a self-reported questionnaire and semi-structured interviews. The data analysis was conducted with social network analyses, comparison between groups and content analyses. Study I examined gender and cultural similarities among adolescents (109 seventh to ninth graders) in patterns of networking (i.e. face-to-face, Facebook connections and peer academic support) at a multicultural Finnish school. Study II investigated the peer selection and influence effects of 100 seventh graders (at Time 1) over one year in terms of the intensity of socio-digital participation and friendship ties. Study III aimed to identify different participation profiles among 253 sixth to ninth graders in various sociodigital activities and to assess systematic differences in social networking relationships. The results revealed that gender and cultural backgrounds are important factors in differentiating students’ networking patterns. Female students were more inclined to use Facebook to connect with other female classmates, whereas males were equally likely to connect with either gender via Facebook. On the other hand, bicultural students were the most likely to network with their classmates in face-to-face connections and Facebook contacts. Further, friendship dynamics with peers played an important role in influencing intensity of students’ interest-driven socio-digital practices to become similar with that of peers. Yet, students were not likely to select peers as friends based on similar intensity of interest-driven socio-digital participation. In terms of academic support with peer, no gender similarities were found in academic support networks, although female students were more apt to engage in academic support than their male counterparts. Bicultural students appeared to engage in academic support with peers from majority and minority cultures. In addition, students with different profiles of socio-digital practices (i.e. basic participators, gaming-oriented participators and creative participators) presented distinct patterns in social networks and digital competences. In particular, the reciprocal values in hanging out, liking and media multiplexity were highest for creative participators, whereas gaming-oriented participators were less socially active than their peers. The socio-digital expertise of creative participators was socially recognized by larger groups of peers than in the other groups. Based on these findings, schools should provide systematic and structural support for students in terms of digital competences and creative use of digital technologies. To that end, it would be crucial to engage digitally competent students to share their skills by tutoring to make use of peer influences in interest-driven digital practices.

Sosiodigitaalinen osallistuminen, ystävyys ja akateeminen tuki 6. – 9. luokkalaisten keskuudessa Suomessa Väitöskirjassa tarkasteltiin kuinka suomalaisten oppilaiden sosiodigitaalinen osallistuminen, ts. tietokoneilla ja mobiililaitteilla internetissä sekä sosiaalisessa mediassa tapahtuva toiminta, liittyy ikätovereiden välisiin ystävyyssuhteisiin sekä kouluapuun. Tarkoituksena oli tutkia erityisesti sukupuolten ja kulttuuritaustojen välistä samankaltaistumista henkilökohtaisissa Facebook- ja kouluapuverkostoissa. Lisäksi tutkimus pyrki selvittämään vertaisiin kohdistuvan valinnan ja vertaisten vaikutuksen seurauksia heidän keskenään muodostamiinsa ystävyysverkostoihin sekä sosiodigitaaliseen osallistumiseen. Lopuksi tarkasteltiin erilaisia sosiaalisiin verkostoihin liittyviä sosiodigitaalisen osallistumisen profiileja. Tutkimuksen osallistujat olivat 6. – 9. luokkien oppilaita Etelä-Suomesta. Aineisto kerättiin kyselylomakkeiden ja haastattelujen avulla. Tutkimuksen aineisto analysoitiin verkostoanalyysin, ryhmien keskinäisen vertailun ja sisällönanalyysin menetelmin. Ensimmäisessä osatutkimuksessa tarkasteltiin sukupuoleen ja kulttuuriin liittyviä samankaltaisuuksia murrosikäisten nuorten (109 oppilasta 7. – 9. luokilta) kaveriverkostoissa, Facebookissa sekä kouluapuverkostoissa yhdessä monikulttuurisessa suomalaisessa koulussa. Toisessa osatutkimuksessa tutkittiin sadan seitsemäsluokkalaisen vertaisvalinnan ja -vaikutuksen seurauksia heidän sosiodigitaaliseen osallistumiseensa ja ystävyyssuhteisiinsa. Kolmas osatutkimus tarkasteli oppilaiden erilaisia sosiodigitaalisen osallistumisen profiileja ja eroja oppilaiden sosiaalisissa verkostosuhteissa. Tutkimukseen osallistui 253 oppilasta 6 – 9 luokilta. Tulokset osoittivat, että sukupuoli ja kulttuuritausta ovat tärkeitä tekijöitä oppilaiden verkostosuhteiden erilaistumisessa. Tytöt hakeutuivat useammin Facebookissa yhteen muiden tyttöjen kanssa, kun taas pojat olivat yhtä suurella todennäköisyydellä yhteydessä molempiin sukupuoliin. Toisaalta kaksikulttuuriset oppilaat verkostoituivat kaikkein todennäköisimmin erilaisia taustoja omaavien luokkatovereiden kanssa sekä henkilökohtaisten yhteyksien että Facebookin kontaktien kautta. Ikätovereiden kanssa solmittujen ystävyyssuhteiden muutokset edistivät oppilaiden sosiodigitaalisten käytäntöjen muuttumista samankaltaisiksi kuin ikätovereilla. Oppilaat eivät kuitenkaan tyypillisesti valinneet ikätovereita ystävikseen sosiodigitaalisen osallistumisen samankaltaisuuden perusteella. Kouluapuverkostot eivät valikoituneet sukupuolten samankaltaisuuksien perusteella, vaikka tytöt olivatkin poikia sitoutuneempia kouluapuun. Kaksikulttuuriset opiskelijat osallistuivat kouluapuverkostoihin yhtä lailla sekä enemmistökulttuureita että kansainvälisiä taustoja edustavien ikätovereidensa kanssa. Lisäksi erilaisen sosiodigitaalisen profiilin omaavat oppilaat (ts. perusosallistujat, pelaamisorientoituneet osallistujat ja luovat osallistujat) erottuivat toisistaan selvästi verkostosuhteissaan ja digitaalisissa kompetensseissa. Erityisesti vastavuoroiset suhteet hengailuverkostoissa, suosio vertaisten keskuudessa ja median päällekkäiskäyttö oli tyypillisintä luovilla osallistujilla, kun taas pelaamisorientoituneet osallistujat olivat sosiaalisesti vähemmän aktiivisia kuin ikätoverinsa. Luovien osallistujien sosiodigitaalinen osaaminen oli sosiaalisesti tunnustetumpaa ikätoverien keskuudessa kuin muilla ryhmillä. Tutkimusten tulosten pohjalta voidaan esittää, että koulujen tulisi tarjota systemaattista ja rakenteellista tukea digitaalisten kompetenssien ja digitaalisten teknologioiden luovaan käyttöön. Tätä varten olisi välttämätöntä osallistaa digitaalisesti taitavat oppilaat tutoroimaan toisia oppilaita. Näin voitaisiin hyödyntää nuorten vertaisvaikutusta digitaalisissa ympäristöissä.